Blue Oil, premier groupe punk féminin au Québec - Desfossés, Félix B. (Ici Radio-Canada, 2019)

L'adaptation de chanson dans l'album ”Cœur vagabond” de Bïa. Une brise de Brésil - Abbrugiati, Perle (ATeM – Archiv für Textmusikforschung, 2019)
Perle Abbrugiati's article explores Coeur vagabond/Coraçao vagabundo, the fourth record by the French-Brazilian artist Bïa, released in 2006. The bilingual album comprises an equal number of Brazilian-Portuguese adaptations from French songs and French adaptations from Brazilian songs. The aim of the present article is to identify the strategies applied in the translation of songs. To this end, the article's author herself uses translation within the framework of a comparative approach, confronting Bïa's translations with her own literal translations (not suitable to be sung) of the original lyrics. The objective is not to trace 'mistranslations' but to point out in how many different and intricate ways a translation can be faithful while being creative, and in what way and to what degree the song translator may take the liberty of 're-semantisation'.
Keywords: Chanson; traduction

Une approche sensible du son - Bertin, Raymond (Jeu : revue de théâtre, 2019)
Article sur l'artiste sonore Nancy Tobin.

“Portrait en Noir et Blanc”: Chico Buarque em francês por Bïa Krieger [“Portrait en Noir et Blanc”: Chico Buarque en français par Bïa Krieger] - Cassiano, Raissa Conde (Tradução em Revista, 2019)

Jouer les femmes : les concerts de musique contemporaine au Québec - Couture, Ariane (Recherches féministes, 2019)

Keyboard Fantasies: The Beverly Glenn-Copeland Story - Dixon, Posy (Greenwich Entertainment et Modern Films, 2019)

Monique Leyrac. Le roman d'une vie - Dompierre, François (Éditions La Presse, 2019)

We Appreciate Power: A Multimodal Critical Discourse Analysis of Grimes' Music Video Posted on YouTube - Enguídanos Gómez, Adrià (Université autonome de Barcelone, 2019)
The aim of this dissertation is to produce a multimodal critical discourse analysis of Grimes' video We Appreciate Power. This will serve to explore issues of ideology, identity and multilingualism in both the music video and the YouTube polylogues generated in the same web page. In this work I suggest that Grimes adopts a poststructuralist view that inherits Haraway's cyborg concept (1991) in this piece of multimedia. I claim that Grimes wanted to show the conflictive moral boundaries that the idea of the cyborg and trans-humanism casts upon Western civilization, such as the loss of free will but also the transgression of problematic dichotomies. The fact that the comment section of the video is available to use might signal that Grimes wanted to raise awareness about trans-humanism. By doing virtual ethnography research, examples of discussion about the relationship between the video and the studied polylogues will be examined regarding the notions of the cyborg and multilingualism.

Je donnerai de la joie. Entretiens avec Dina Bélanger - Gauthier, Jacques (Éditions Novalis, 2019)
Dina Bélanger (1897-1929) s’est donnée très jeune au Christ, ne voulant que lui plaire dans l’intimité de la prière. À vingt-quatre ans, elle renonce à une brillante carrière de pianiste pour entrer au couvent des Religieuses de Jésus-Marie à Québec. Elle expérimente l’union mystique avec la Trinité par le cœur eucharistique de Jésus. Béatifiée par Jean-Paul II en 1993, elle laisse à l’Église et au monde un héritage spirituel d’une richesse exceptionnelle, qui rappelle celui de Thérèse de l’Enfant-Jésus, qu’elle avait prise pour patronne, avec sainte Cécile. Dans le sillage de ses ouvrages sur Thérèse de Lisieux et Marie-Léonie Paradis, Jacques Gauthier nous offre un autre entretien chaleureux et instructif avec une «?amie de Dieu?» qui avait dit avant de mourir, à trente-deux ans?: «?Je donnerai de la joie.?» Ses questions pertinentes facilitent cet échange intime avec Dina qui, par l’intermédiaire de son autobiographie, témoigne d’une sainteté unique et inspirante.

Why Lhasa de Sela Matters - Goodman, Fred (University of Texas Press, 2019)

Ton métier, le mien, le Québec. Fragments de correspondance amoureuse et politique 1962-1993 - Julien, Pauline; Godin, Gérald (Leméac Éditeur, 2019)
Dix ans après la parution de La renarde et le mal peigné,quatre cents nouvelles lettres échangées entre Gérald Godin (1938-1994) et Pauline Julien (1929-1998) ont été découvertes dans leurs fonds d’archives respectifs. Soixante-dix d’entre elles ont été choisies par Emmanuelle Germain et Jonathan Livernois, dans cette édition qui vient compléter le portrait forgé en 2009. On y retrouvera les débuts de la relation entre le journaliste et la chanteuse, les longues tournées en Europe de Pauline Julien, la maladie de Godin, puis celle, en filigrane, de Julien. De nouveaux aspects apparaîtront également : l’érotisme de plusieurs de leurs échanges ; les rapports d’amitié ; les aléas d’une vie familiale où un jeune homme de vingt-cinq ans doit s’occuper de deux adolescents, alors que Julien doit concilier sa vie professionnelle et sa vie de mère ; l’épuisement des dernières années, tandis que les tournées européennes sont de plus en plus difficiles pour Julien. Les lettres réunies ici permettront également aux lectrices et aux lecteurs de revivre de grands moments de l’histoire québécoise, vue à la hauteur de ses acteurs : le « Vive le Québec libre ! » lancé par Pauline Julien à Niamey, en 1969, interrompant le ministre fédéral Gérard Pelletier ; la crise d’Octobre et l’emprisonnement sur lequel on ne reviendra guère ; la campagne électorale de 1976, l’enthousiasme et la victoire, inattendue ; l’engagement du député puis ministre Gérald Godin. Ce n’est donc pas un hasard si ce petit livre est sous-titré « Fragments de correspondance amoureuse et politique ». La suture des deux univers, de l’intime et du public, de l’amour et du politique, y est plus claire que jamais.

The Women’s Art Society of Montreal and Its Place in History, 1894-2019 - Keays, Cathy (Autoédition, 2019)

La mélancolie dans la chanson québécoise contemporaine : Tu m'intimides de Mara Tremblay, La forêt des mal-aimés de Pierre Lapointe, À Paradis City de Jean Leloup - Laliberté St-Pierre, Audrey (Université Laval, 2019)
La chanson québécoise actuelle paraît réconcilier la chanson dite «à texte» et la chanson populaire, comme ce fut le cas pour la chanson engagée des années 1970. Si le thème de l’engagement soutenait plusieurs œuvres chansonnières de cette décennie, celui de la mélancolie semble pouvoir définir une certaine tendance actuelle. Ce mémoire s’intéresse au thème de la mélancolie dans la chanson québécoise contemporaine et plus précisément dans les albums Tu m’intimides de Mara Tremblay, La forêt des mal-aimés de Pierre Lapointe et À Paradis City de Jean Leloup. À la fois auteurs, compositeurs et interprètes, ces trois artistes s’inscrivent dans le champ populaire de la chanson québécoise en créant des œuvres où le texte et la musique mettent la mélancolie en valeur. Dans cette étude, la mélancolie est étudiée en fonction de trois aspects, soit l’être mélancolique, la temporalité mélancolique et l’espace mélancolique. C’est à travers l’exploration de ces trois aspects que sont analysées les chansons du corpus, surtout à partir des textes, mais en considérant aussi certains éléments musicaux.

« Cohérence d’une œuvre métissée » : extrait de thèse de doctorat (2007) - Makdissi-Warren, Katia (Circuit, 2019)
Publisher: Circuit, musiques contemporaines

Katia Makdissi-Warren : étapes et œuvres marquantes - Pascal, Noémie (Circuit, 2019)
Publisher: Circuit, musiques contemporaines

L’univers de Katia Makdissi-Warren (un diagramme) - Pascal, Noémie (Circuit, 2019)
Publisher: Circuit, musiques contemporaines

"A Jewish Maestra and a Lady too": Reflections on Femininity in the Career of Ethel Stark - Rachwal, Maria N. (Canadian Jewish Studies, 2019)
Ethel Stark (1910-2012) was one of the most important conductors and concert violinists in Canada in the Twentieth century. This article highlights how an Austro-Canadian Jewish woman who lived outside the constraints of conventional domesticity, both navigated through and defied the ideals of the “Cult of True Womanhood” and spearheads a movement of feminism in music. I argue that Stark’s exposure to Jewish cultural traditions of social justice and womanhood in her childhood formed a critical dimension of her feminist activism later in her life, and in particular in the founding of The Montreal Women’s Symphony Orchestra (1940).

“Saw You in the Dark”: Exploring Rufus Wainwright’s Emotional Vulnerability in Fan-Captured Live Performance Videos - Salerno, Stephanie (Performance Matters, 2019)

The Expression of the Tragic in the Chamber Cantata Dați-Mi Lampa Lui Aladin [Give Me Aladdin's Lamp] by Dora Cojocaru - Seraz, Roxana Maria (Musicology Papers, 2019)
Dora Cojocaru is recognized as an outstanding representative of the Cluj school of composition, but also as a strong voice in Romanian musicology. While her musicological output includes books, studies, articles, radio programs, conference papers, master classes and scientific communication sessions, her most important contribution remains the book entitled Creația lui Gyӧrgy Ligeti în contextul stilistic al secolului XX [Gyӧrgy Ligeti's Work in the Stylistic Context of the Twentieth Century], which was the first book about Ligeti that appeared in the Romanian musicological landscape. Dora Cojocaru’s compositional portrait can be drawn by following the language characteristics and compositional devices used in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. The composer’s work is characterised by a propensity for chamber music. The composer confesses that it is also a consequence of the fact that this genre comes with a plethora of expressive possibilities. In terms of the musical language used by the composer, its first characteristic is the concern to avoid repetition in expression and the variation of an already used musical material. This is strikingly evident in the chamber cantata Dați-mi lampa lui Aladin [Give Me Aladdin's Lamp]. Another peculiarity is the construction based on a developmental discourse, while a third characteristic is the frequent construction of the discourse based on an economy of means and on a musical material consisting of only a few notes. In the case of this cantata, it is essential to note the historical context, which is closely linked to the symbolic title suggesting the composer’s desperate desire to bring her brother back to life, although she is aware that this is only possible by magic. The composer’s choice of lyrics is derived from the fact that Trakl’s and Rilke’s texts allude to the theme of death, which is one of the frequent themes of late Expressionism, and are therefore pervaded by a tragic note, in tune with the composer’s musical intentions. If we follow the text-music relationship, we notice some extremely significant moments, in which music creates sonic images that are suggestive of the message of the text.

Reality Sounding: Annesley Black’s not thinking about the elephants - Tan, Anthony (Circuit, 2019)
This paper presents an analysis of Annesley Black’s not thinking about the elephants (2018), for saxophone quartet and live electronics. Written for Montreal’s Quasar Saxophone Quartet, this work explores concepts of suppression and emergence through traditional musical dimensions such as melody, counterpoint, and form, but also through contemporary musical dimensions such as psychoacoustics (difference tones), theatrical elements, and live electronics. Black’s practice engages critically with the compositional process itself by formulating dialectic relationships between material and compositional strategies (both intuitive and systematic). This work encourages the listener to engage in a multidimensional listening experience where conceptual extremes become a catalyst for the building of narrative and tension.
Publisher: Circuit, musiques contemporaines

Création contemporaine et partage des traditions : à la rencontre de Katia Makdissi-Warren - Tremblay, Vicky (Circuit : musiques contemporaines, 2019)
Un article de la revue Circuit, diffusée par la plateforme Érudit.
Publisher: Circuit, musiques contemporaines